2014
DOI: 10.1007/s00428-014-1673-8
|View full text |Cite
|
Sign up to set email alerts
|

Large (>3.8 cm) clear cell renal cell carcinomas are morphologically and immunohistochemically heterogeneous

Abstract: Heterogeneity is an inherent event to tumour development that is lately receiving much attention in oncologic research. The topic is being addressed primarily at the molecular level, and results are promising. However, translation to practical medicine is still pending. Our intention in this study is to approach the problem in a series of clear cell renal cell carcinomas with the tools that pathologists use in routine practice. Three randomly selected areas of 48 clear cell renal cell carcinomas prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…This fact makes difficult to quantify the nature and extent of ITH, if present, in most CCRCC. Although pathologists recognize by naked eye whitish hard areas related to sarcomatoid transformation, as well as hemorrhagic and/or necrotic foci, there is a significant amount of ITH hidden in apparently homogeneous areas, as recently reported [ 10 12 ]. Furthermore, an incomplete tumor sampling may justify the unexpected aggressive behavior that some low-grade CCRCC show [ 12 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This fact makes difficult to quantify the nature and extent of ITH, if present, in most CCRCC. Although pathologists recognize by naked eye whitish hard areas related to sarcomatoid transformation, as well as hemorrhagic and/or necrotic foci, there is a significant amount of ITH hidden in apparently homogeneous areas, as recently reported [ 10 12 ]. Furthermore, an incomplete tumor sampling may justify the unexpected aggressive behavior that some low-grade CCRCC show [ 12 ].…”
Section: Discussionmentioning
confidence: 95%
“…Although pathologists recognize by naked eye whitish hard areas related to sarcomatoid transformation, as well as hemorrhagic and/or necrotic foci, there is a significant amount of ITH hidden in apparently homogeneous areas, as recently reported [ 10 12 ]. Furthermore, an incomplete tumor sampling may justify the unexpected aggressive behavior that some low-grade CCRCC show [ 12 ]. The present work has shown the relationship between cell type and Grade in CCRCC, since a mixture of conventional clear and granular cells determines high tumor Grade (G3/G4) in more than 83 % of cases.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mathematical analysis of the data obtained has demonstrated that the most relevant parameters for predicting intratumor heterogeneity in CCRCC are tumor size, eosinophilic cellularity, Fuhrman grade, and the expression of Ki67 and COX2 (20). Neither CAIX nor BAP-1 have been found to be significantly associated with heterogeneity in this study (20), despite the two markers being directly involved in tumor aggressiveness (24,25).…”
Section: Immunohistochemical Heterogeneitymentioning
confidence: 92%
“…Andere interessante prognostische Marker existieren im KNK, wie zum Beispiel Ki-67, ein Marker für den Proliferationsindex, BAP-1 und COX-2 [36]. Eine Überexpression dieser Proteine könnte ein Zeichen für ein schlechtes Überleben sein.…”
Section: Niereunclassified